Breaking taboo : perspectives of African Civil Society on innovative sources of financing development (Commonwealth Foundation LondonGB, 2008)
Looks at current and prospective revenue streams for development. Examines the origin, current operation and prospects for the airlines levy & UNITAID as well as the currency Transaction Tax proposal and its suggested implementation. Deals with the digital solidarity levy and the tax with migrants' remittances.
Bibliography: p. 55